Ownership mix of addiction treatment centres in the USA. (27th June 2011) - David, Guy; Lederhandler, Margo; Acevedo-Perez, Victoria
The dominant presence of private Addiction Treatment Centres (ATCs) raises questions about how changes in ownership mix affect access to and quality of care. This paper examines the relationship between an ATC's ownership choice and the ownership mix in its market. Organisational and market characteristics are considered by using data from the National Survey of Substance Abuse Treatment Services, North American Industry Classification System, Internal Revenue Service's Business Master File, US Census Bureau Population Estimate Survey, Uniform Crime Reporting Program Data and Local Area Unemployment Statistics. We use linear probability models to link the facility's choice of ownership with the ownership status of its competitors. The results indicate that the value of being non-profit is higher in markets where many ATCs are non-profit and lower in markets where many are for-profit. The likelihood of a non-profit status appears to be more influenced by the presence of incumbent non-profits, rather than by high earnings or longevity.